Barriers to uptake of Open-Source automated insulin delivery Systems: Analysis of socioeconomic factors and perceived challenges of adults with type 1 diabetes from the OPEN survey. (March 2023) - O'Donnell, Shane; Cooper, Drew; Chen, Yanbing; Ballhausen, Hanne; Lewis, Dana M.; Froment, Timothée; Anna Gajewska, Katarzyna; Tappe, Adrian; Skinner, Timothy; Cleal, Bryan; Braune, Katarina
Highlights: OS AID has been shown to improve clinical outcomes and quality of life. This is the first study to identify the most common barriers to uptake of OS AID among those currently not using such a system. The findings highlight the implications of inequalities in access to OS AID and how they might be addressed. Abstract: Aims: Social and technical trends are empowering people with diabetes to co-create or self-develop medical devices and treatments to address their unmet healthcare needs, for example, open-source automated insulin delivery (AID) systems. This study aims to investigate the perceived barriers towards adoption and maintaining of open-source AID systems. Methods: This is a multinational study based on a cross-sectional, retrospective web-based survey of non-users of open-source AID. Participants (n = 129) with type 1 diabetes from 31 countries were recruited online to elicit their perceived barriers towards building and maintaining of an open-source AID system. Results: Sourcing the necessary components, lack of confidence in one's own technology knowledge and skills, perceived time and energy required to build a system, and fear of losing healthcare provider support appear to be major barriers towards the uptake of open-source AID. Conclusions: This study identified a range of structural and individual-level barriers to uptake of open-source AID. Some of these individual-level barriers may be overcome over time through the peer support of the DIY online community as well as greater acceptance of open-source innovation among healthcare professionals. The findings have important implications for understanding the possible wider diffusion of open-source diabetes technology solutions in the future.